2003
DOI: 10.1002/erv.509
|View full text |Cite
|
Sign up to set email alerts
|

Longer‐term implications of responsiveness to ‘thin‐ideal’ television: support for a cumulative hypothesis of body image disturbance?

Abstract: Brief exposure to thin-ideal media images has been shown to have a small but consistent negative impact on women and girls' body dissatisfaction. The present study aimed to examine the consequence of these small changes in body dissatisfaction for the development of body image over time. A sample of 80 adolescents (mean age ¼ 17.2 years) completed measures of body dissatisfaction, drive for thinness, and drive for muscularity. Two years earlier they had viewed either 20 appearance-related television commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 32 publications
5
17
0
2
Order By: Relevance
“…These findings are consistent with other research that suggests that thin ideal media exposure in adolescents is associated with body dissatisfaction and eating disorder symptomatology [19, 39, 40]. …”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other research that suggests that thin ideal media exposure in adolescents is associated with body dissatisfaction and eating disorder symptomatology [19, 39, 40]. …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the use of VAS scores, while ideally suited to the short exposure durations involved in this study (because VAS scales are unmarked), does not permit interpretation of the clinical significance of changes in psychological state. Thus, while causal relationships between changes in state VAS scores and exposure to same-sex models can be stated with some degree of certainty due to the experimental design employed, the implications of these effects on unhealthy body change behaviors must be made cautiously-the absence of longitudinal data; the use of an adult sample where any evidence of unhealthy body change preexists; the short exposure durations employed; the short-lived effects of exposure measured in the study; and the lack of clinically validated measures of state change make it impossible to confirm that it is an accumulation of emotional reactions to idealized bodies that contributes to the development of unhealthy body change [50]. To do so would require further research to confirm that the inherent instability of psychological states actually precedes the development of negative body image and unhealthy body change attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Other related limitations include the fact that we did not ask participants whether they had previously seen the episodes in question or whether they were regular viewers of each show, which may have had an affect on our results. Finally, we only measured short-term changes in body image and mood, and it remains unclear what the long-term effects of exposure to such programs might be (e.g., see Hargreaves & Tiggemann, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also suggested that exposure to Web sites that feature anorexic women has a negative impact on women's corporeal experiences (Bardone-Cone & Cass, 2007). Moreover, Hargreaves and Tiggemann (2003) reported that study participants whose body image was most negatively affected by exposure to images of the thin ideal had greater body dissatisfaction and drive for thinness 2 years later, which the authors claimed was consistent with a cumulative hypothesis of the effects of media exposure on body image development.…”
mentioning
confidence: 84%